Case report: Right coronary artery to left ventricular fistula complicated with coronary artery dilation presenting as persistent cardiogenic ischemic chest pain - Wang, Yuehai; Zhang, Yuqiang; Wang, Fei; Xue, Yuzeng (Frontiers in Cardiovascular Medicine, 2023)
We reported a patient with a fistula of the right coronary artery to the left ventricle, accompanied by dilation of the right coronary artery and persistent chest pain. This patient underwent surgical fistula closure surgery, but the fistula recurred. Persistent chest pain reappeared after encountering COVID-19 infection. We analyzed the mechanism of persistent myocardial ischemic chest pain caused by coronary artery fistula in this patient, the impact of surgery on the patient's disease, the possible mechanism of COVID-19 causing persistent ischemic chest pain in this patient, and the possible mechanism of metoprolol in alleviating myocardial ischemic chest pain in this patient.